Marketing assistance for instant herbal drink products in the KBU Sehat home industry group, Banjar Regency - Isnaini, Isnaini; Asnawati, Asnawati; Yuliani, Rahma (Universitas Muhammadiyah Magelang, 2025)
The PKK (Family Welfare Movement) mothers of KBU Village have been producing an instant herbal drink named